An ACE2 decoy can be administered by inhalation and potently targets omicron variants of SARS‐CoV‐2. Issue 11 (23rd September 2022) - Zhang, Lianghui; Narayanan, Krishna K; Cooper, Laura; Chan, Kui K; Skeeters, Savanna S; Devlin, Christine A; Aguhob, Aaron; Shirley, Kristie; Rong, Lijun; Rehman, Jalees; Malik, Asrar B; Procko, Erik
Abstract: Monoclonal antibodies targeting the SARS‐CoV‐2 spike (S) neutralize infection and are efficacious for the treatment of COVID‐19. However, SARS‐CoV‐2 variants, notably sublineages of B.1.1.529/omicron, have emerged that escape antibodies in clinical use. As an alternative, soluble decoy receptors based on the host entry receptor ACE2 broadly bind and block S from SARS‐CoV‐2 variants and related betacoronaviruses. The high‐affinity and catalytically active decoy sACE22 .v2.4‐IgG1 was previously shown to be effective against SARS‐CoV‐2 variants when administered intravenously. Here, inhalation of aerosolized sACE22 .v2.4‐IgG1 increased survival and ameliorated lung injury in K18‐hACE2 mice inoculated with P.1/gamma virus. Loss of catalytic activity reduced the decoy's therapeutic efficacy, which was further confirmed by intravenous administration, supporting dual mechanisms of action: direct blocking of S and turnover of ACE2 substrates associated with lung injury and inflammation. Furthermore, sACE22 .v2.4‐IgG1 tightly binds and neutralizes BA.1, BA.2, and BA.4/BA.5 omicron and protects K18‐hACE2 mice inoculated with a high dose of BA.1 omicron virus. Overall, the therapeutic potential of sACE22 .v2.4‐IgG1 is demonstrated by the inhalation route and broad neutralization potency persists against highly divergent SARS‐CoV‐2 variants. Synopsis: SARS‐CoV‐2 infects cells via interactions between the viral Spike and ACE2 on host cells. A soluble derivative of ACE2 that is engineered for tight Spike affinity is effective against newly circulating SARS‐CoV‐2 variants and is efficacious through multiple mechanisms and routes of administration. An engineered decoy receptor, sACE22.v2.4‐IgG1, binds tightly to Spike proteins and blocks replication in vitro and in vivo of SARS‐CoV‐2 omicron variants. Proteolytic activity of the decoy receptor contributes to its therapeutic efficacy to increase survival of SARS‐CoV‐2 infected K18‐hACE2 transgenic mice. The decoy receptor is therapeutically effective via intravenous infusion and inhalation routes. Abstract : SARS‐CoV‐2 infects cells via interactions between the viral Spike and ACE2 on host cells. A soluble derivative of ACE2 that is engineered for tight Spike affinity is effective against newly circulating SARS‐CoV‐2 variants and is efficacious through multiple mechanisms and routes of administration.